2010
DOI: 10.1002/pola.24239
|View full text |Cite
|
Sign up to set email alerts
|

Redox initiated cationic polymerization: Silane‐N‐aryl heteroaromatic onium salt redox couples

Abstract: In this article, a new route for the synthesis of N‐aryl heteroaromatic onium salts by the direct copper catalyzed arylation of pyridine, substituted pyridines, isoquinoline, and acridine with diaryliodonium salts is described. It was demonstrated that these N‐aryl heteroaromatic onium salts undergo facile platinum or rhodium‐catalyzed reduction by silanes bearing SiH groups. The reduction of N‐aryl heteroaromatic onium salts generates Brønsted acids. When this redox reaction was carried out in situ in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Acylsulfonium salts are also highly efficient compared to iodonium salts as shown by Molleo et al [190] In that study, an interesting tuning of the gel time can be performed through the adjustment of the ppm level of metallic catalyst (e.g. 30 s gel time to 110 s when changing the Pt catalyst level from 8 to 2 ppm).N-Arylheteroaromaticonium salts can also be proposed though a difficult RCP of oxetanes was observed [191] when highly successful for activated epoxides and vinylethers.…”
Section: Other Catalystsmentioning
confidence: 92%
“…Acylsulfonium salts are also highly efficient compared to iodonium salts as shown by Molleo et al [190] In that study, an interesting tuning of the gel time can be performed through the adjustment of the ppm level of metallic catalyst (e.g. 30 s gel time to 110 s when changing the Pt catalyst level from 8 to 2 ppm).N-Arylheteroaromaticonium salts can also be proposed though a difficult RCP of oxetanes was observed [191] when highly successful for activated epoxides and vinylethers.…”
Section: Other Catalystsmentioning
confidence: 92%
“…Such a property is highly researched in industries as it allows to produce colorless coatings. [231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246] Photolysis experiments realized with the D12/EDB and D12/Iod systems proved the photobleaching to be extremely fast compared to that observed for the other dyes. It can be thus concluded that the superiority of D12 over the other dyes relies in its fast interaction with the two co-initiators, speeding up the polymerization process so that the oxidative and the reductive cycles could concomitantly contribute to the formation of initiating radicals (See Figure 14).…”
Section: Push-pull Dyes Based On Indane-13-dionementioning
confidence: 99%
“…It has to be noticed that, in-situ generation of strong acids in resins is already reported in the literature, except that these strong acids have only been obtained by mean of redox reactions involving the use of transition metals. Thus, the generation of strong acids by reaction of a copper-catalyzed reduction of iodonium salts with benzoins, [242,243] or the platinum-catalyzed reduction of iodonium salts with boranes or silanes [244][245][246][247] have previously been reported in the literature. Besides, traces of residual metals can constitute a major impediment for further use of polymers.…”
Section: 3-bis(dicyanomethylidene)indanementioning
confidence: 99%
“…Several groups have developed several onium salt series as photo-cationic initiators for the cationic polymerization of cyclic ethers, alkyl vinyl ethers, and epoxides [ 10 , 11 , 12 , 13 , 14 , 15 ]. The sulfonium and iodonium salts were indefinitely stable without photo-irradiation, but under photo-irradiation, initiating species were generated, which polymerized rapidly without inhibition or retardation, indicating the presence of a latent initiator.…”
Section: Introductionmentioning
confidence: 99%